Clinical evaluation of coronally advanced flap with or without acellular dermal matrix graft on complete defect coverage for the treatment of multiple gingival recessions with thin tissue biotype - (:unkn) unknown (WILEY, 2014)
Aim: The objective of this study was to compare acellular dermal matrix graft (ADM) combination with coronally advanced flap (CAF) on complete defect coverage, aesthetics and patient satisfaction with CAF alone for multiple recessions with gingival thickness (GT) <0.8mm. Materials and MethodsForty-eight Miller Class I multiple recessions 3mm were divided into test (CAF+ADM) and control (CAF) groups. At baseline and 12months, recession height (RH), keratinized tissue height (KT), GT, mean and complete defect coverage were evaluated. Patient satisfaction, root coverage aesthetic score (RES) and the correlation between GT and defect coverage were also assessed. ResultsBaseline RH in CAF+ADM and CAF groups was 3.250.34mm and 3.21 +/- 0.26mm, respectively. Mean and complete defect coverage were 94.84% and 83.33% in test group, 74.99% and 50.00% in control group, respectively. Inter-group differences were found to be statistically significant for RH reduction, attachment gain, KT and GT increase, mean defect coverage and RES in favour of test group (p<0.05). There was a significant positive correlation between GT and mean defect coverage (p<0.05). Conclusion: Coronally advanced flap in association with ADM can be proposed as a valid approach for the treatment of multiple recessions with thin tissue biotype.
Keywords: acellular dermal matrix graft; coronally advanced flap; gingival thickness; multiple recessions; root coverage aesthetic score; AUTOGENOUS CONNECTIVE-TISSUE; PERIODONTAL PLASTIC-SURGERY; 2 SURGICAL-PROCEDURES; MILLER CLASS-I; ROOT-COVERAGE; POSITIONED FLAP; COLLAGEN MATRIX; THICKNESS; OUTCOMES; PREDICTOR